2011
DOI: 10.3748/wjg.v17.i2.197
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in NF-κB, PXR, LXR, PPARγ and risk of inflammatory bowel disease

Abstract: Common PXR and LXR polymorphisms may contribute to risk of IBD, especially among never smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 74 publications
2
59
0
Order By: Relevance
“…Conceivably, genes involved in the NF-κB pathway are interesting candidate genes for chronic inflammatory disorders, including CD and UC. In 2 mouse models of colitis, although not the same physiological condition as in humans, a strong linkage has been observed between a polymorphism in the NFKB1 gene and the susceptibility to UC and CD [37][38][39]. However, given that some authors have suggested that the role of NFKB in the regulation of apoptosis is not yet defined, our group studied its levels in various stages of CD.…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, genes involved in the NF-κB pathway are interesting candidate genes for chronic inflammatory disorders, including CD and UC. In 2 mouse models of colitis, although not the same physiological condition as in humans, a strong linkage has been observed between a polymorphism in the NFKB1 gene and the susceptibility to UC and CD [37][38][39]. However, given that some authors have suggested that the role of NFKB in the regulation of apoptosis is not yet defined, our group studied its levels in various stages of CD.…”
Section: Discussionmentioning
confidence: 99%
“…Excess or inappropriate activation of NF-B has been observed in IBD patients and experimental IBD animal models (2). It has been demonstrated that the blockade of NF-B activation with flavanoid agents might be an effective strategy in abrogating experimental IBD (6,26).…”
Section: Discussionmentioning
confidence: 99%
“…Information on diet, lifestyle, weight, height, medical treatment, environmental exposures, and other socioeconomic factors was collected at enrollment using questionnaires and interviews as described in detail elsewhere (28,(35)(36)(37). In short, a food-frequency questionnaire (FFQ) assessed diet consumption in 12 categories of predefined responses, ranking from "never" to "eight times or more per day."…”
Section: Dietary and Lifestyle Questionnairementioning
confidence: 99%